Impact of neurological diseases on family planning: A single-center experience. Issue 44 (30th October 2020) - Alanazy, Mohammed H.; Asiri, Alanood; Edrees, Maha F.; Abuzinadah, Ahmad R.
Abstract : Abstract: This cross-sectional study aimed to assess the impact of epilepsy, myasthenia gravis (MG), and multiple sclerosis (MS) on pregnancy and family planning decision-making in a cohort of Saudi women. Women with epilepsy, MG, and MS were recruited consecutively at the time of their follow-up visits at a neurology clinic. Data were collected using 3 standardized questionnaires, and presented using descriptive statistics. A logistic regression was performed to determine variables associated with decisions regarding abstaining from pregnancy and encouraging other women to conceive. A total of 272 (83 epilepsy, 69 MG, and 120 MS) women with a mean age of 29.9 ± 8.0 years participated. The proportion of women who abstained from or postponed pregnancy was 41.2% and 31.4%, respectively. The concerns mentioned most often were disease worsening during pregnancy, peripartum and postpartum, side effects of medications on the unborn child, and inability to care for the child. Older age was independently associated with the decision to abstain from pregnancy (odds ratio [OR] 1.14, 95% confidence interval [CI] 1.04 - 1.25). Higher knowledge levels were independently associated with encouraging other women to have children (OR 1.3, 95% CI 1.11–1.53). Over 50% of women reported that they were not counseled on issues related to pregnancy and childbirth. In conclusion, we identified a major influence of epilepsy, MG, and MS on pregnancy and family planning. Comprehensive counseling programs are needed to help women with these neurological diseases make informed family-planning decisions. Abstract : Supplemental Digital Content is available in the text